The demands and determinants of success of the tackle and ruck between the pool and knockout stages of the Men`s International World Rugby Sevens Series - Hendricks, S.; de Klerk, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Rugby Sevens (henceforth called `Sevens`) is an Olympic sport that has grown rapidly worldwide, both in terms of participation and commercialisation. The most frequent physical-technical contests are the tackle and ruck. Success in Sevens is, in part, dependent on the teams ability to repeatedly "win" these physical-technical contests. In addition to the Olympics, World Rugby (the sports governing body) has run a World Sevens Series since 1999, featuring national teams from all rugby nations. The series has grown to ten tournaments and the competition structure for each tournament uses a pool stage (four teams in each pool) to knock-out stage format, whereby teams will play against all opponents in their pools with the top two teams from each pool progressing through to the knockout stages. Studies in Rugby Union have shown that match variables in the knockout-stages may differ compared to the pool stages in terms of frequency of occurrence, however this is not know for Sevens. Therefore, the purpose of this study was to compare tackle and ruck frequencies between pool and knockout matches during the Men`s International World Rugby Sevens Series and also determine which technical determinants increase the likelihood of tackle success within each stage of the tournament. METHODS: Video analysis of all matches during the 2018/2019 International Men`s Rugby Sevens World Series was conducted (n=449 matches). This equated to 21 226 tackle contact events and 6 345 rucks events. Each tackle event was further coded for tackle descriptors (type of tackle, direction of contact, point of body contact) and tackle outcomes (successful and unsuccessful). The unpaired T-test was used to compare the frequency of tackle and ruck events per match between pool- and knockout matches. Logistic regression was used to identify tackle determinants that were associated with tackle success within each tournament stage. RESULTS: No differences were found between the mean tackles per match of pool and knockout stages (Pool 47.5, 95% CI 46.5-48.6 vs Knockout 46.9, 95% CI 45.7-48.0). There was a significant difference (p